TINJAUAN KONSEP KEBERLANJUTAN PADA KAWASAN PERMUKIMAN KAMPUNG NELAYAN TAMBAK LOROK DALAM PROGRAM KAMPUNG WISATA BAHARI - Maya Nugraha; Agung Dwiyanto (Jurnal Arsitektur ARCADE, 2023)
Abstract: Coastal areas are border areas between sea and land, generally coastal areas are known as slum areas and low levels of education. But now the government has created a marine tourism village program, in an effort to preserve coastal areas, because generally residents are reluctant to be relocated considering that the majority of their jobs are fishermen. The Tambak Lorok Fisherman's Village itself has been undergoing the Marine Tourism Village program since 2015, the sustainable aspects applied to Tambak Lorok have not been fully seen. Various problems still arise, including tidal flooding and infrastructure facilities to support sustainability itself. Aspects of sustainability that can be seen include economic, social, and ecological aspects. The existence of the Maritime Tourism Village program in Tambak Lorok has helped the community's economic sector in the form of a market, meeting the social needs of residents in the form of communal spaces that can be used continuously. So that it can be concluded, sustainability in communal public spaces has been used by residents for various kinds of social activities.Keyword: sustainability, communal space, architectureAbstrak: Wilayah pesisir merupakan wilayah perbatasan antara laut dan daratan, umumnya wilayah pesisir dikenal kawasan kumuh dan tingkat pendidikan rendah. Namun kini pemerintah telah membuat program kampung wisata bahari, dalam upaya pelestarian wilayah pesisir, karena umumnya warga enggan untuk direlokasi mengingat mayoritas pekerjaannya adalah nelayan. Kampung Nelayan Tambak Lorok sendiri telah menjalani program Kampung Wisata Bahari sejak 2015, aspek berkelanjutan yang diterapkan pada Tambak Lorok belum sepenuhnya terlihat. Berbagai permasalahan masih muncul, antara lain banjir rob dan sarana prasarana sebagai penunjang keberlanjutan itu sendiri. Aspek keberlanjutan yang dapat dilihat antara lain aspek ekonomi, sosial, dan ekologi. Adanya program Kampung Wisata Bahari di Tambak Lorok telah membantu sektor ekonomi warga dalam bentuk pasar, memenuhi kebutuhan sosial warga berupa ruang komunal yang dapat digunakan secara berlanjut. Sehingga dapat disimpulkan, keberlanjutan dalam ruang publik komunal hingga kini digunakan warga untuk berbagai macam aktivitas sosial.Kata Kunci: keberlanjutan, ruang komunal, arsitektur